Is the use of Lactobacillus reuteri probiotic efficient as adjunctive therapy in the treatment of periodontitis? A systematic review - Tricoly, Tainá da Silva [UNESP]; Ferreira, Camila Lopes [UNESP]; Lima, Victória Clara da Silva [UNESP]; de MARCO, Andrea Carvalho [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Editora Cubo, 2023)
Objective: This systematic review had the purpose to validate the probiotic Lactobacillus reuteri as adjuvant therapy in the periodontal treatment of periodontitis, by the analysis of randomized controlled trial, controlled clinical trial, and observational studies. Material and Methods: Search keys related to the subject were defined, and the following databases were used as search strategies: MEDLINE via PubMed, Scopus, Web of Science, Cochrane Central Controlled Trials Registry, and EMBASE. The data selection and study were performed by two independent evaluators: first, they selected the article by title and abstract and subsequently qualified according to the bias risk analysis. A narrative synthesis has been performed based on the data obtained from the best-quality articles. After data extraction, their heterogeneity was analyzed, and a meta-analysis was performed. Results: In general, the results of the meta-analysis were positive for the use of probiotics as an adjuvant treatment. Considering the limitations of the comparisons between the analyzed articles studied, the conclusion was that probiotics may provide supplementary benefits to the treatment of periodontitis, with improvement in bleeding on probing rates and probing depth.
O uso do probiótico Lactobacillus reuteri como terapia adjuvante no tratamento da periodontite é eficaz? Uma revisão sistemática
Keywords: Lactobacillus reuteri; Periodontal diseases; Periodontitis; Probiotics; Systematic review